Development of nutraceutical formulations based on mycelium of Pleurotus ostreatus and Agaricus bisporus - Cardoso, Rossana V.C. (2017)
The importance of improving people's quality of life has aroused the interest of the food industry to develop new products with functional characteristics that may be associated with possible beneficial effects on human health, either preventive or therapeutic aspects. Functional foods and nutraceuticals present in its composition bioactive substances that provide medical benefits and, therefore, have aroused the interest of many consumers around the world. Mushrooms are a source of proteins, vitamins, minerals, and especially bioactive compounds. These compounds, including ergosterol, phenolic compounds, tocopherols, ascorbic acid and carotenoids, have been associated with antioxidant, anti-inflammatory, antimicrobial and cytotoxic properties, among others attributed to mushrooms and associated to its promoting health effects. Following this approach, the present work aimed to develope nutraceutical formulations based on mycelium of Agaricus bisporus L. and Pleurotus ostreatus (Jacq. Ex Fr.) P. Kumm. The present study highlights the potential of in vitro culture as a tool to improve production of bioactive compounds by two different mushroom species. Accordingly, A. bisporus and P. ostreatus were studied for their composition in phenolic acids and sterols, antioxidant activity (DPPH radicals scavenging, reducing power, β-carotene bleaching inhibition and TBARS formation inhibition), anti-inflammatory effect (by down-regulating LPS-stimulated NO in RAW264.7 cells) and cytotoxic activity (using MCF-7, NCI-H460, HeLa, HepG2 and PLP2 cell lines). Therefore, the mycelia of A. bisporus and P. ostreatus was cultured in different solid and liquid media, and further submitted to solid-liquid extraction processes; these assayed species showed differences in the growth rate and yielded biomass. Overall, P. ostreatus mycelia showed higher contents of ergosterol and phenolic compounds (but the mycelia of A. bisporus produced in PDA presented a higher amount of p-hydroxybenzoic acid) and stronger antioxidant activity than the corresponding fruting body. On the other hand, P. ostreatus and A. bisporus did not show anti-inflammatory activity. However, P. ostreatus showed cytotoxicity in human tumor cell lines in opposition to A. bisporus, that didn't present cytotoxic activity. In conclusion, the results show that these mushrooms are a good source of compounds with antioxidant and cytotoxic capacity, with variations among species.